2021
DOI: 10.1002/ajmg.a.62542
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular findings in Williams–Beuren Syndrome: Experience of a single center with 127 cases

Abstract: Williams-Beuren syndrome (WBS) is a rare, microdeletion syndrome characterized by facial dysmorphisms, intellectual disability, a friendly personality, cardiovascular and other abnormalities. Cardiovascular defects (CVD) are among the most prevalent characteristics in WBS, being supravalvular aortic stenosis (SVAS) the most frequent, followed by peripheral pulmonary stenosis (PPS). A comprehensive retrospective review of medical records of 127 patients with molecular diagnosis of WBS, in a period of 20 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…In Argentina, a study reported four cases of surgical intervention for MVP [ 26 ]. Despite this, most previous studies [ 25 , 27 , 28 ] found no need for mitral surgery in WS due to the lower severity of MVP in WS [ 27 ]. According to Cha et al [ 25 ], 33% of patients with MR in WS were moderate to severe, accompanied by left ventricular and left atrial enlargement.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In Argentina, a study reported four cases of surgical intervention for MVP [ 26 ]. Despite this, most previous studies [ 25 , 27 , 28 ] found no need for mitral surgery in WS due to the lower severity of MVP in WS [ 27 ]. According to Cha et al [ 25 ], 33% of patients with MR in WS were moderate to severe, accompanied by left ventricular and left atrial enlargement.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, it is extremely difficult to trace the natural progression of cardiovascular diseases in patients with WS from the time of birth according to a previous study [ 17 ]. Most patients with WS had undergone cardiology evaluations before they were diagnosed with WS in real-world practice, as per previous studies [ 17 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one fetus was prenatally diagnosed with SVAS and no case with peripheral pulmonary stenosis, whereas these two features are the most frequent cardiac lesions described postnatally in WBS (50% and 22%, respectively). 16 The common aspect of the hourglass-shaped lesion described postnatally could be difficult to detect in a fetus whose ascending aorta is smaller.…”
Section: Q1123 Microduplicationmentioning
confidence: 99%
“…One case with premature closure of the ductus arteriosus (PCDA) was reported by Srinivasan et al 12 . About 80% of WBS patients suffer from cardiovascular defects, which are the main cause of morbidity and mortality in WBS 1,13–16 . These patients require early diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%